Vitamin D, Depression and Headache - Results from the Tromsø Study and an intervention study with vitamin D - Kjærgaard, Marie (2013)
The papers of this thesis are not available in Munin: 1. Paper I. Kjærgaard, M., R. Joakimsen, and R. Jorde: 'Low serum 25-hydroxyvitamin D levels are associated with depression in an adult Norwegian population', Psychiatry Research (2011), vol. 190(2-3):221-225. Available at http://dx.doi.org/10.1016/j.psychres.2011.06.024 2. Kjærgaard, M., K. Waterloo, C.E. Wang, B. Almås, Y. Figenschau, M.S. Hutchinson, J. Svartberg, and R. Jorde: 'Effect of vitamin D supplement on depression scores in people with low levels of serum 25-hydroxyvitamin D: nested case-control study and randomised clinical trial', British Journal of Psychiatry (2012), vol. 201(5):360-368. Available at http://dx.doi.org/10.1192/bjp.bp.111.104349 3. Kjærgaard M, C.E.A. Wang, K. Waterloo, and R. Jorde: 'A study of the psychometric properties of the Beck Depression Inventory-II, the Montgomery and Åsberg Depression Rating Scale and the Hospital Anxiety and Depression Scale in a healthy population' (manuscript) 4. Kjærgaard M, A.E. Eggen, E.B. Mathiesen, and R. Jorde: 'Association Between Headache and Serum 25-Hydroxyvitamin D; the Tromsø Study: Tromsø 6', Headache (2012), vol.52(10):1499-1505. Available at http://dx.doi.org/10.1111/j.1526-4610.2012.02250.x Vitamin D is well known for the effect in bone metabolism and calcium regulation. In the past decade increasing evidence that vitamin D might be important in other areas has emerged. Especially glucose metabolism, cardiovascular disease and infectious diseases have been investigated. In addition, several population studies have shown that an association between vitamin D and depression might be of importance. Furthermore, increasing headache prevalence with higher latitudes has led to theories about a relation between headache and vitamin D. Our analyses from the Tromsø Study confirm that low levels of vitamin D are associated with higher depression scores independent of lifestyle factors that might influence vitamin D. However, whether vitamin D has any effect in treatment of depression cannot ...